Advances in pharmacotherapy of vestibular and ocular motor disorders. (3rd July 2019) - Zwergal, Andreas; Strupp, Michael; Brandt, Thomas
ABSTRACT: Introduction : Vertigo and dizziness are common chief complaints of vestibular and ocular motor disorders (lifetime prevalence 30%). Treatment relies on physical, pharmacological, psychological and rarely surgical approaches. Eight groups of drugs are currently used in vestibular and ocular motor disorders, namely anti-vertiginous, anti-inflammatory, anti-menière's, anti-migrainous medications, anti-depressants, anti-convulsants, aminopyridines and agents that enhance vestibular plasticity. Areas covered : The purpose of this review is to summarize the pharmacological characteristics and clinical applications of medications that are used for peripheral, central and functional vestibular and ocular motor disorders. The level of evidence for the respective drugs is described alongside the pathophysiological premises supporting their use. The authors place particular focus on translation and back-translation in vestibular pharmacological research and the repurposing of known drugs for new indications and rare disorders. Expert opinion : The use of drugs in vestibular and ocular motor disorders is often based on open-label, non-controlled studies and expert opinion. In the future, strong evidence derived from RCTs is needed to support the effectiveness and tolerability of these therapies in well-defined vestibular and ocular motor disorders. Vestibular pharmacological research must be guided by a better understanding of the molecular targets relevant in the pathophysiology of vestibular and ocular motor disorders.